North Korean Paradoxes Circumstances, Costs, and Consequences of Korean Unification - Wolf, Charles Jr (RAND Corporation, 2005)
Analyzes economic, political, and security issues associated with Korean unification. Considers how the North Korean system might unravel, leading to possible unification, and what the capital costs of unification would be under differing circumstances and assumptions. Compares points of relevance and nonrelevance between the German experience with unification in the 1990s and what might occur in Korea.